Pengaruh Penerapan Metode SAS (Struktural Analitik Sintetik) terhadap Kemampuan Membaca Permulaan Siswa Kelas I Sekolah Dasar Negeri 13 Pontianak Timur - Dwi Putri Larasati; Siti Halidjah; Asmayani Salimi (Departement of Mathematics Education, 2024)
This research aims to find out the effect of applying the SAS (Synthetic Structural Analytical) method on the beginning reading ability of class I students at State Elementary School 13 East Pontianak. The method used in this research is an experimental method with a quasi experimental design. The population in this study was all class I students, totaling 55 students. Sampling used nonprobability sampling techniques and obtained a sample of class IA totaling 27 students as the control class and class IB totaling 28 students as the experimental class. Data collection techniques use measurement techniques and direct observation techniques. The data collection tool used was an oral initial reading test. Based on data analysis, the average posttest score for the experimental class = 77.64 and the average posttest score for the control class = 73.02. The results of hypothesis testing using the t-test with the polled variance formula obtained tcount of 1.329 and ttable (α = 5% and dk = 28 + 28 – 2 = 54) of 0.6837, which means tcount > ttable, then Ha is accepted. Based on the results of the effect size (ES) calculation, the ES value = 0.42. Thus, it can be concluded that the application of the SAS (Synthetic Structural Analytical) method has an influence on the initial reading ability of class I students at State Elementary School 13 East Pontianak by 42%.